1999
DOI: 10.1002/etc.5620181122
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of amphibian embryos and tadpoles to Mimic® 240 LV insecticide following single or double exposures

Abstract: Abstract-Mimic 240 LV is a novel, narrow-spectrum insecticide containing the active ingredient tebufenozide. Tebufenozide mimics the action of the insect molting hormone ecdysone and shows specific activity toward larval Lepidoptera. In Canada, Mimic 240 LV has been proposed for use in forest pest control, whereas a different formulation has been registered for use in agriculture. We examined the effects of single and double pulses of Mimic 240 LV (tebufenozide) on the development, growth, and predator avoidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
2
26
1
1
Order By: Relevance
“…This insu$cient physical barrier of protection is reported for other pesticides for amphibians and "sh (Hashimoto et al, 1982;Wiegand et al, 2000). In contrast, Berrill et al (1998) and Pauli et al (1999) reported that for amphibians the jelly coat surrounding the embryo provided a protective layer during growth and development. The protection of the forming embryo from pesticide contamination appears to be strongly dependent on tested species and investigated pesticides.…”
Section: Uptake and Metabolism Of Ipumentioning
confidence: 91%
See 2 more Smart Citations
“…This insu$cient physical barrier of protection is reported for other pesticides for amphibians and "sh (Hashimoto et al, 1982;Wiegand et al, 2000). In contrast, Berrill et al (1998) and Pauli et al (1999) reported that for amphibians the jelly coat surrounding the embryo provided a protective layer during growth and development. The protection of the forming embryo from pesticide contamination appears to be strongly dependent on tested species and investigated pesticides.…”
Section: Uptake and Metabolism Of Ipumentioning
confidence: 91%
“…Therefore, amphibians of these stage with complete operculum were used in exposure investigations. Pauli et al (1999) con"rmed that tadpoles at…”
Section: Ewects Of Ipu Exposure On Tadpolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns praguicidas e seus metabólitos têm sido encontrados como poluentes no fundo e superfície de águas, no solo (Kolpin et al, 2004;Fava et al, 2005;Worrall e Besien, 2005), e na atmosfera (Dubus et al, 2000;Duyzer, 2003) e são prováveis responsáveis pela perda da biodiversidade e a deterioração de habitats naturais (Pauli et al, 1999). O aumento da consciência dos riscos relacionados ao uso intensivo de praguicidas tem levado a uma atitude mais crítica pela sociedade agrícola, gerando mudanças concernentes ao uso para evitar danos ambientais e gerar maior segurança alimentar (Saba e Messina, 2003).…”
Section: Praguicidasunclassified
“…Some pesticides and their metabolites have been considered as pollutants of the bottom and surface of waters, soil [1][2][3] and atmosphere [4]. They are likely responsible for the loss of biodiversity and deterioration of natural habitats [5]. Increased awareness on the risks related to the intensive use of pesticides has led to a more critical attitude by the agricultural society to prevent future environmental damage [6].…”
Section: Introductionmentioning
confidence: 99%